If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + -19 = 2y + 8 Reorder the terms: -19 + 5y = 2y + 8 Reorder the terms: -19 + 5y = 8 + 2y Solving -19 + 5y = 8 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. -19 + 5y + -2y = 8 + 2y + -2y Combine like terms: 5y + -2y = 3y -19 + 3y = 8 + 2y + -2y Combine like terms: 2y + -2y = 0 -19 + 3y = 8 + 0 -19 + 3y = 8 Add '19' to each side of the equation. -19 + 19 + 3y = 8 + 19 Combine like terms: -19 + 19 = 0 0 + 3y = 8 + 19 3y = 8 + 19 Combine like terms: 8 + 19 = 27 3y = 27 Divide each side by '3'. y = 9 Simplifying y = 9
| log(5x)-38=-28 | | 4b-6=6b | | -8(x-5)+2=-7x+7 | | 9x=(27/9)*6 | | 7(x+5)=8x+6 | | (23-3y)/(y-6) | | 9y-2=38+y | | 13x-(3x+12)-12x=-5x+3 | | -2(-3-x)=7 | | 2/3=x/25-x | | 13=2w+3(w+6) | | 6x+4=-28-2x | | -7v+5(v-3)=-23 | | 3x+19=3x-103 | | 12-t+25=23 | | 4*9-5y=26 | | G-5.2=-18.73 | | 4x-5(2)=26 | | 9-17+4x-x=0 | | 3(4x-3)-4(3x+8)=7(x-6) | | 12-4=5x-25 | | 75=P+3.75P | | 9+6=54153 | | f(x)=4x-3x^2-5 | | 7x-y/-1 | | 10-2x=1000-2(100)+4(10)-2(2)+20(200)-3(20)+6(50)+8(30)+4(40) | | 2p+1=107 | | d=p+-33 | | 3b-8=7b-100 | | -2(w-5)=-18 | | -6n-20=-12n+4(1-3n) | | 10-2px=1000-2(100)+4(10)-2(2)+20(200)-3(20)+6(50)+8(30)+4(40) |